AdS 3-manifolds and Higgs bundles - Alessandrini, Daniele; Li, Qiongling (Proceedings of the American Mathematical Society, 2018)
In this paper we investigate the relationships between closed AdS -manifolds and Higgs bundles. We have a new way to construct AdS structures that allows us to see many of their properties explicitly, for example we can recover the very recent formula by Tholozan for their volume.